2021
DOI: 10.1111/ane.13447
|View full text |Cite
|
Sign up to set email alerts
|

Electroencephalography of mechanically ventilated patients at high risk of delirium

Abstract: Objective Neurophysiological exploration of ICU delirium is limited. Here, we examined EEG characteristics of medical‐surgical critically ill patients with new‐onset altered consciousness state at high risk for ICU delirium. Materials and methods Pre‐planned analysis of non‐neurological mechanically ventilated medical‐surgical ICU subjects, who underwent a prospective multicenter randomized, controlled EEG study (NCT03129438, April 2017–November 2018). EEG characteristics, according to the 2012 ACNS nomenclatu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 39 publications
0
3
0
1
Order By: Relevance
“… 6 Another prospective multicenter randomized controlled study revealed a 7% increase in prevalence of delirium in mechanically-ventilated patients with observable seizures and status epilepticus on EEG. 11 Both findings suggested a significant contribution of seizures to the evolution of delirium. 6 , 11 In another study, nonconvulsive status epilepticus and interictal discharges were found in 12% and 30% of elderly delirium patients, respectively, irrespective of the etiologies.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“… 6 Another prospective multicenter randomized controlled study revealed a 7% increase in prevalence of delirium in mechanically-ventilated patients with observable seizures and status epilepticus on EEG. 11 Both findings suggested a significant contribution of seizures to the evolution of delirium. 6 , 11 In another study, nonconvulsive status epilepticus and interictal discharges were found in 12% and 30% of elderly delirium patients, respectively, irrespective of the etiologies.…”
Section: Discussionmentioning
confidence: 96%
“… 11 Both findings suggested a significant contribution of seizures to the evolution of delirium. 6 , 11 In another study, nonconvulsive status epilepticus and interictal discharges were found in 12% and 30% of elderly delirium patients, respectively, irrespective of the etiologies. 12 It can be theorized that the presence of an epileptic focus in the cortex promoted encephalopathy via widespread neuronal metabolism alteration, specifically in the functions of the cholinergic, serotonergic, and catecholaminergic systems in subcortical areas, which can produce diffuse cortical hypoactivity.…”
Section: Discussionmentioning
confidence: 96%
“…Fritz et al ( 33 ) found that a longer duration of intraoperative EEG suppression is associated with a higher occurrence of delirium. Eskioglou et al ( 34 ) found that the EEG of patients with delirium in the intensive care unit may demonstrate burst suppression, rhythmic or periodic patterns, and seizures or status epilepticus. Patients with delirium also show increased slow-wave activity involving the occipitoparietal and frontal cortex with disruption of functional connectivity ( 35 ).…”
Section: Discussionmentioning
confidence: 99%
“…A inflamação tem sido relacionada a fisiopatologia do delirium, sendo que a razão plaqueta-linfócito (PLR) relatada como um marcador da resposta inflamatória em várias doenças (doença cardiovascular, lesão renal aguda, câncer, etc). Desta Eskioglou et al (2021), compararam achados de eletroencefalograma (EEG) -exame não invasivo e amplamente disponível -em pacientes delirantes versus não delirantes. Pacientes delirantes apresentaram maior frequência na supressão de surtos (10 vs 0%, p=0,02), nos padrões rítmicos/periódicos (43% vs 22%, p=0,03) e na atividade epileptiforme (7 vs 0%, p=0,05), independente da sedação ou analgesia.…”
Section: Identificaçãounclassified